A Preliminary Investigation on Processing, Mechanical and Thermal Properties of Polyethylene/Kenaf Biocomposites with Dolomite Added as Secondary Filler. (13th October 2015) - Shamsuri, Ahmad Adlie; Mohd Zolkepli, Mohammad Naqiuddin; Mohamed Ariff, Azmah Hanim; Sudari, Ahmad Khuzairi; Abu Zarin, Mazni
Abstract : In this preliminary investigation, dolomite was added to the low-density polyethylene/kenaf core fiber (LDPE/KCF) biocomposites by using an internal mixer at 150°C, followed by compression molding at the same temperature. The dolomite contents were varied from 0 to 18 wt.%. The processing and stabilization torques, the stock and stabilization temperatures, the tensile and impact strengths, and the thermal decomposition properties of the prepared biocomposites have been characterized and analyzed. The processing recorder results of the LDPE/KCF biocomposites indicated that the stabilization torques and stabilization temperatures have increased with the addition of dolomite. Mechanical testing results showed that the presence of dolomite has increased the tensile stress, tensile modulus, and impact strength of the LDPE/KCF biocomposites. Thermogravimetric analysis results displayed that the thermal decomposition properties of the biocomposites have also increased with the increase of the dolomite content. This research led to the conclusion that the addition of dolomite in lower amounts (<20 wt.%) could act as a secondary filler for improving the processing, mechanical and thermal properties of LDPE/KCF biocomposites without surface treatments of the natural fiber.